The Integration of Islamic Values in the History of Islamic Civilization into English Language Teaching - Mh Saifudin; Siti Rohimah (South Sulawesi Education Development (SSED), 2025)
This study explores the integration of Islamic values derived from the history of Islamic civilization into English language teaching in madrasahs. The research employs a literature review methodology, analyzing secondary data from scholarly sources to develop a comprehensive framework for this integration. By utilizing materials such as the contributions of Muslim scholars, Islamic architectural heritage, and the development of Islamic civilization, the study aims to contextualize English learning while fostering students’ religious character. The findings highlight that integrating Islamic values enhances the relevance and engagement of English learning, making it more meaningful for students. However, challenges such as students' resistance to integrative approaches are noted, which can be mitigated through innovative strategies like teacher collaboration and contextual teaching methods. The study underscores the theoretical and practical implications of this integration, contributing to holistic education theory and providing educators with practical guidelines. Limitations of the research, including its conceptual nature and focus on madrasahs, necessitate further empirical studies to validate and refine the proposed model.